Deciphering biodiversity and interactions between bacteria and microeukaryotes within epilithic biofilms from the Loue River, France - Zancarini, Anouk (Sci Rep, 2017)
Epilithic river biofilms are complex matrix-enclosed communities harboring a great diversity of prokaryotic and eukaryotic microorganisms. Interactions between these communities and the relative impacts of environmental factors on their compositions are poorly understood. In this study, we assessed the spatio-temporal variation in the diversity and composition of bacterial and microeukaryotic communities within biofilms in a French river. Significant changes were found in the composition of these microbial communities over the sampling period and between the upstream and downstream stations. In addition, the beta diversity of the bacterial community tended to decrease along the river, mostly as a result of turnover. These changes could be caused by the different water temperatures and geological and hydrological river contexts at the sampling sites (from karst landscape to river plain). Finally, our network analysis showed multiple correlations among dominant OTUs. Among them, negative correlations between Rhodobacteraceae and two other dominant groups of photosynthetic microorganisms (cyanobacteria and diatoms) were particularly interesting, which raises the question of what environmental factors trigger the changes occurring in benthic microbial photosynthetic communities.